2023
DOI: 10.1002/jmri.28824
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Effects of the CEP128 Gene on Radiotherapy‐Related Brain Injury: A Longitudinal Structural Study Using Multi‐Parametric Brain MR Images

Abstract: BackgroundThe promoter variant rs17111237 in the CEP128 closely relates to radiotherapy (RT)‐related brain necrosis in nasopharyngeal carcinoma (NPC) patients.PurposeTo explore RT‐related dynamic alterations in brain morphology and their potential genetic mechanism, and to explore the modulatory effects of CEP128 genetic variants on RT‐related brain morphological alterations in NPC patients.Study TypeProspective, longitudinal.PopulationOne hundred one patients with histopathologic ally‐proven NPC (age 41.64 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The reduced morphometric similarity in the group of individuals with chronic schizophrenia aligns with previous research morphometric similarity findings as well as general default mode dysfunction in high-risk, early-onset and chronic schizophrenia (Morgan et al, 2019; Whitfield-Gabrieli et al, 2009; Yao et al, 2023). A recent study demonstrated that morphometric similarity was positively correlated with the likelihood of cellular network structures forming axonal connections (Lin et al, 2024). In schizophrenia, axonal dysconnectivity between networks might lead to the micro-structural and functional connectivity deficits observed across various age groups affected by the disease, including children, adolescents, and adults (Barth et al, 2023; Heuvel and Sporns, 2019; Kelly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced morphometric similarity in the group of individuals with chronic schizophrenia aligns with previous research morphometric similarity findings as well as general default mode dysfunction in high-risk, early-onset and chronic schizophrenia (Morgan et al, 2019; Whitfield-Gabrieli et al, 2009; Yao et al, 2023). A recent study demonstrated that morphometric similarity was positively correlated with the likelihood of cellular network structures forming axonal connections (Lin et al, 2024). In schizophrenia, axonal dysconnectivity between networks might lead to the micro-structural and functional connectivity deficits observed across various age groups affected by the disease, including children, adolescents, and adults (Barth et al, 2023; Heuvel and Sporns, 2019; Kelly et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…EOS1 exhibited differences in MSN strength in multiple functional and von Economo atlas, whereas EOS2 displayed abnormalities only in MSN strength within motor networks. Previous studies have demonstrated that high/low MSN strength implies that the cellular structures of similar/differentiated networks could be more/less likely to form axonal connections to each other [ 41 ]. Changes in the brain develop rapidly from childhood to adolescence as myelination and synapse pruning [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of JMRI, an article by Lin et al 7 applies MSN to a cohort of 101 patients with NPC treated with radiotherapy in a well‐designed longitudinal study design and shows that there are detectable changes in the mean MSN at 3‐ and 6‐month post radiotherapy. The MSN abnormalities involved the bilateral temporal and frontal lobes as well as left occipital lobe and left parietal lobe.…”
mentioning
confidence: 99%
“…Beyond the important impact in treatment of NPC, patients with non‐NPC malignancies such as brain metastases or high‐grade gliomas, would also potentially benefit. While it remains to be seen if MSN or similar computational methods will be incorporated into the imaging of patients undergoing radiation therapy, or if treatments based on the biology of CEP128 will be developed, the work by Lin et al 7 takes us an important step further toward those goals.…”
mentioning
confidence: 99%